Defect characterization, advanced etching techniques, and large field-of-view imaging for metalenses - Zhu, Chenxu (University of Waterloo, 2025)
Metalenses, made of nanostructures, have attracted significant interest for their ability to overcome the limitations of traditional lenses. This thesis provides a thorough study on the design, fabrication, and characterization of high-performance metalenses using metasurface technology. It underscores the interactions among fabrication imperfections, advanced nanofabrication techniques, and imaging performance across a large field of view (FOV). Defects in metalenses introduced during fabrication can significantly affect their optical performance. Chapter 3 carried out a unique experimental analysis using real-fabricated devices to investigate the impact of different defects, including inclined sidewall angle, uniform critical dimension bias, non-uniform bias due to the proximity effect, and the notching effect in etching, on parameters such as focal spot intensity, focal length, and Strehl ratio (SR). Our research indicates a 47% decrease in intensity when the sidewall is positively tapered by 4˚, a 15% intensity reduction with a 30 nm deviation in structure size, minimal intensity and focusing quality deterioration with the non-uniform bias, and a 13% intensity decrease along with a significant drop in focusing quality when the notching effect occurs. Our study provides critical insights into the tolerances required for optimal metalens performance and offers recommendations for time and cost savings. Chapter 4 introduces an innovative etching technique that utilizes a three-step C4F8/SF6 plasma etching process with varying gas ratios at different depths. By maintaining the plasma after each step, this continuous three-step process offers enhanced flexibility for tuning the etching of high aspect ratio (HAR) nanostructures, resulting in smooth and vertical profiles. By using the optimal gas ratio, metalens nanostructures with diameters of 71 nm and heights of 1 μm were successfully created, with feature size variation kept to less than 10 nm. This proposed continuous multi-step approach significantly improves the controllability of silicon nanopillar etching, which is crucial for achieving precise phase control and effectively manipulating light in metalens applications. Building on these advancements, Chapter 5 details the design and fabrication of a single-layer metalens that achieves a broad FOV of 120° at a near-infrared wavelength of 940 nm. The metalens features a simple structure consisting of a metallic aperture paired with a single-layer metasurface. To optimize the phase profile of the metalens, a ray-tracing algorithm was utilized. The resulting enhanced metalens demonstrates commendable focusing efficiency (35-61%) and diffraction-limited imaging (SR > 0.8), positioning it as a promising candidate for applications in imaging, sensing, and integrated photonic systems.
Keywords: Metalens; Fabrication; Defects; Large field-of-view